Temporal and spatial distribution of Precambrian red beds and their formation mechanisms - Hongwei Kuang; Huaqing Bai; Nan Peng; Kening Qi; Yuchong Wang; Xiaoshuai Chen; Yongqing Liu (Geosystems and Geoenvironment, 2022)
Red beds are irrefutable evidence of important geological events; understanding their formation mechanism and sedimentary environment provide insights about Earth's history and the evolution of life. In this paper, Precambrian red beds from over 70 outcrops in nearly 30 regions in different countries are statistically assessed using their lithology, sedimentary environment, and spatio-temporal distribution. Twelve sets of red beds are identified, five of which are distributed globally; the other sets are regional or local. The depositional environments for red beds are varied. They include terrestrial (aeolian, alluvial, and fluvial) and shallow marine environments (dominantly, tidal and glacial marine), as well as the transition areas from shallow to deep-water environments. While the former two are dominant environments, the latter has fewer occurrences – most of which are concentrated in strata of the Ediacaran Period. Red beds are lithologically diverse; terrestrial red beds are mainly composed of conglomerate and sandstone, while shallow marine red beds primarily consist of siltstone, mudstone, and carbonate rocks. The formation of red beds is directly controlled by the concentration of dissolved Fe and O2 content, and penecontemporaneous geological events. Here, they are sorted into two groups based on their chronological coupling with glaciations, the assembly and breakup of supercontinents, eustatic sea-level changes, the flourishing of photoautotrophs like cyanobacteria, as well as δ13C and 87Sr/86Sr isotope anomalies. The formation of the first group of red beds is closely related to the Paleoproterozoic and Neoproterozoic glaciations, the Great Oxidation Event, and the Neoproterozoic Oxygenation Event. Much of the dissolved Fe scavenged from seawater during oxygenation events precipitated into banded iron formations (BIF). The transmittance of light through water reduced during glaciations. It prevented the production of O2 and limited Fe2+ oxidation – which worked as a protector for oceanic Fe re-accumulation. The melting of glaciers improved the availability of light which restarted the production of photosynthetic O2 that aided the formation of red beds. The formation of the second group of red beds was aided by supercontinent fragmentation that created many shallow margin habitats for photoautotrophs, facilitating O2 production. The appearance of this group of red beds coincides with and is geochemically supported by pulses of O2 increase recorded by Cr and C isotopes, as well as by iron speciation data. Future research should examine how Precambrian red beds can be used to systematically decode paleoenvironment changes.